Analysis of sustainable practices in costume creation of selected Filipino cosplayers - Llave, James Andrew R.; Quiñola, Kim Agatha (Quezon City 2025, 2025)
Cosplay, defined as dressing up and acting as a fictional character, is an emerging subculture in the Philippines. However, like in clothing production, cosplay costumes also generate textile and plastic wastes. (West & Smith, 2017) This qualitative study analyzed the sustainable practices in the costume creation of selected Filipino cosplayers. Fourteen participants were purposively selected and interviewed regarding their costume creation process and sustainable practices; their own understanding of sustainability; and the factors affecting their approach towards sustainability. Key to the cosplayers' creation process are inspiration and planning, wherein they choose a character to cosplay and reconstruct its costume. They cross-check the complexity of the costume design with their own resources, such as budget and materials. They apply sustainable practices into their costume creation, such as upcycling, recycling, thrifting and maximizing their materials. After their use, costumes are often repurposed or repaired. There is also modular design, wherein parts of the costume can be worn for another character or as everyday clothing. For the cosplayers, their understanding of sustainability mainly involves practical goals like costume longevity, waste reduction, and cost reduction. However, sustainability in cosplay is hindered by several factors, such as time, budget and skills. Their limitations would result to low-quality construction and one-time use of costumes. It is also notable that commitment to accuracy, especially for complex character designs, hinders sustainable practices, since it would require special materials and techniques that are prone to generate more waste. Further research could investigate the after-use practices of cosplayers, such as storage, maintenance and waste management of costumes, within the framework of sustainability.
In partial fulfillment for the Degree of Bachelor of Science in Clothing Technology
Thesis
Keywords: Sustainable design; Textile waste -- Philippines; Costume creation; Filipino cosplay